Condon domain phase diagram for silver - Kramer, R.B.G.; Egorov, V.S.; Gasparov, V.A.; Jansen, A.G.M.; Joss, W. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We present the Condon domain phase diagram for a silver single crystal measured in magnetic fields up to 28 T and temperatures down to 1.3 K. A standard ac method with a pickup coil system is used at low frequency for the measurements of the de Haas–van Alphen effect (dHvA). The transition point from the state of homogeneous magnetization to the inhomogeneous Condon domain state (CDS) is found as the point where a small irreversibility in the dHvA magnetization arises, as manifested by an extremely nonlinear response in the pickup voltage showing threshold character. The third harmonic content in the ac response is used to determine with high precision the CDS phase boundary. The experimentally determined Condon domain phase diagram is in good agreement with the theoretical prediction calculated by the standard Lifshitz–Kosevich formula.